2017
DOI: 10.1007/s13361-016-1586-7
|View full text |Cite
|
Sign up to set email alerts
|

Near-UV Photodissociation of Tryptic Peptide Cation Radicals. Scope and Effects of Amino Acid Residues and Radical Sites

Abstract: , where X = A, C, D, E, F, G, H, K, L, M, N, P, Y, and W, were generated by electron transfer dissociation of peptide dications and investigated by MS 3 -nearultraviolet photodissociation (UVPD) at 355 nm. Laser-pulse dependence measurements indicated that the ion populations were homogeneous for most X residues except phenylalanine. UVPD resulted in dissociations of backbone CO─NH bonds that were accompanied by hydrogen atom transfer, producing fragment ions of the [y n ] + type. Compared with collision-induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 58 publications
1
14
0
Order By: Relevance
“…Other z • ‐type ions were observed to expel a thiol radical only upon applying additional CID activation after ETD, in line with reported higher rates of formation of w ‐ions compared with u ‐ions . Also in accordance with previous studies, loss of CH 2 S (46 Da) after collisional activation was only observed for z • ‐ions that contain a Cys residue, but not at the cleavage site. Spectroscopic probing of the structure of these fragment ions is challenging because of the more involved ETD/CID MS n scheme required to produce them, and the inherent lower ion yields as compared with the w ‐type ions; such experiments are reserved for future studies.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…Other z • ‐type ions were observed to expel a thiol radical only upon applying additional CID activation after ETD, in line with reported higher rates of formation of w ‐ions compared with u ‐ions . Also in accordance with previous studies, loss of CH 2 S (46 Da) after collisional activation was only observed for z • ‐ions that contain a Cys residue, but not at the cleavage site. Spectroscopic probing of the structure of these fragment ions is challenging because of the more involved ETD/CID MS n scheme required to produce them, and the inherent lower ion yields as compared with the w ‐type ions; such experiments are reserved for future studies.…”
Section: Resultssupporting
confidence: 90%
“…Cys‐specific ExD pathways have been discussed in several studies . For z • ‐type fragments from Cys‐containing peptides, secondary fragmentation by loss of a 33‐Da neutral fragment is common and is attributed to loss of a thiol radical (SH • ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations